2010
DOI: 10.1002/acp.1696
|View full text |Cite
|
Sign up to set email alerts
|

Children's ability to recall unique aspects of one occurrence of a repeated event

Abstract: Preschool and school-age children's memory and source monitoring were investigated by questioning them about one occurrence of a repeated lab event (n ¼ 39). Each of the four occurrences had the same structure, but with varying alternatives for the specific activities and items presented. Variable details had a different alternative each time; hi/lo details presented the identical alternative three times and changed once. New details were present in one occurrence only and thus had no alternatives. Children mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
68
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 30 publications
5
68
0
Order By: Relevance
“…If the detail is bound tightly with its source, retrieval of the detail is more likely to also lead to retrieval of the corresponding source than if the detail was not tightly bound to source. Alternatively, the repetition of the source with each detail in the event may have provided children with a "label" for the event source, thus aiding retrieval because retrieving a label may spread to retrieval of features associated with the label (Brubacher, Roberts & Powell, 2011; recall that the 'source' needed to be extracted rather than visually observed). A third possibility is that source may be more easily reconstructed if it was encoded in parallel with unique details.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the detail is bound tightly with its source, retrieval of the detail is more likely to also lead to retrieval of the corresponding source than if the detail was not tightly bound to source. Alternatively, the repetition of the source with each detail in the event may have provided children with a "label" for the event source, thus aiding retrieval because retrieving a label may spread to retrieval of features associated with the label (Brubacher, Roberts & Powell, 2011; recall that the 'source' needed to be extracted rather than visually observed). A third possibility is that source may be more easily reconstructed if it was encoded in parallel with unique details.…”
Section: Discussionmentioning
confidence: 99%
“…However, other differences between events may not be so obvious, such as when there is constant variation across individual repetitions of an event. In a recent study, children participated in classroom Binding an event 8 activities on four different days (Brubacher, Glisic, Roberts, & Powell, 2011). Some of the props changed each day, for example, children read a story but it was a different story each day.…”
Section: Types Of Encoding Processesmentioning
confidence: 99%
“…We permitted children with repeated experience to describe the occurrence that they "remembered best" when prompted for episodic information. This was done in two recent repeated event studies (Brubacher, Glisic, Roberts, & Powell, 2010;Brubacher, Roberts & Powell, in press) and is more ecologically valid than choosing the "last time. "…”
mentioning
confidence: 99%
“…This line of research has shown that children's memories are notably different from those of adults (Butler, Gross, & Hayne, 1995;Fivush, 1993;Fivush, Gray, & Fromhoff, 1987;Gross & Hayne, 1998;Reese, 2009;Reese, Haden, & Fivush, 1993). Furthermore, although researchers often consider childhood amnesia to reflect accelerated forgetting in early childhood, prospective studies of children's memory development suggest that at least some of these ''forgotten'' memories might never have been encoded in substantial detail in the first place.…”
mentioning
confidence: 93%
“…A number of researchers have shown that drawing, and talking about that drawing, during a memory interview facilitates children's verbal reports of past experiences (Butler et al, 1995;Drucker, Greco-Vigorito, Moore-Russell, Avaltroni, & Ryan, 1997;Gross & Hayne, 1998Patterson & Hayne, 2011;Wesson & Salmon, 2001). In these studies researchers have manipulated a number of variables including the age of the child, the length of delay CHILDREN'S RECOLLECTION OF DETAILS 433 between the event and the interview, the emotional significance of the target event, and the form of questioning employed during the interview.…”
mentioning
confidence: 99%